'Let the wide world be our teacher' - Abd Razak, Dzulkifli (2010)
WHAT is unique about the Higher Education Minister's 2010 Annual Address last week was the creation of the Liga Bola Sepak Institut Pengajian Tinggi (IPT) or the Higher Education Institutions Football League. Coming within a month of Malaysia's gold medal in the recent SEA Games, the initiative shows the timely support by the ministry to continue with the winning streak. It took two decades to bring back the SEA Games football glory. This new move can only mean that our hope to retain the position would be better the next time around.